Plasticity in the proteome of Emiliania huxleyi CCMP 1516 to extremes of light is highly targeted. Issue 1 (10th June 2013) - McKew, Boyd A.; Lefebvre, Stephane C.; Achterberg, Eric P.; Metodieva, Gergana; Raines, Christine A.; Metodiev, Metodi V.; Geider, Richard J.
Summary: Optimality principles are often applied in theoretical studies of microalgal ecophysiology to predict changes in allocation of resources to different metabolic pathways, and optimal acclimation is likely to involve changes in the proteome, which typically accounts for > 50% of cellular nitrogen (N). We tested the hypothesis that acclimation of the microalga Emiliania huxleyi CCMP 1516 to suboptimal vs supraoptimal light involves large changes in the proteome as cells rebalance the capacities to absorb light, fix CO2, perform biosynthesis and resist photooxidative stress. Emiliania huxleyi was grown in nutrient‐replete continuous culture at 30 (LL) and 1000 μmol photons m −2  s −1 (HL), and changes in the proteome were assessed by LC‐MS/MS shotgun proteomics. Changes were most evident in proteins involved in the light reactions of photosynthesis; the relative abundance of photosystem I (PSI) and PSII proteins was 70% greater in LL, light‐harvesting fucoxanthin–chlorophyll proteins (Lhcfs) were up to 500% greater in LL and photoprotective LI818 proteins were 300% greater in HL. The marked changes in the abundances of Lhcfs and LI818s, together with the limited plasticity in the bulk of the E. huxleyi proteome, probably reflect evolutionary pressures to provide energy to maintain metabolic capabilities in stochastic light environments encountered by this species in nature.